(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The paper presents the problems may be faced by companys during the implemen-tation of ABC system. Effective implementation of the model depends on internal and external factors -to a lesser extent on external factors. Before deciding to apply the model, it is necessary to analyze thecompanies infrastructure that allows the correct measurement, calculation and record of information about generated cost. Resources which should be taken into account during designing the ABC system are employees, acost accounting system, the level of cost information which is desirable.